Murine CD83-positive T cells mediate suppressor functions in vitro and in vivo - Kreiser, Simon; Eckhardt, Jenny; Kuhnt, Christine; Stein, Marcello F.; Krzyzak, Lena; Seitz, Christine; Tucher, Christine; Knippertz, Ilka; Becker, Christoph; Günther, Claudia; Steinkasserer, Alexander; Lechmann, Matthias (Immunobiology, 2015)
The CD83 molecule (CD83) is a well-known surface marker present on mature dendritic cells (mDC). In this study, we show that CD83 is also expressed on a subset of T cells which mediate regulatory T cell (Treg)-like suppressor functions in vitro and in vivo. Treg-associated molecules including CD25, cytotoxic T lymphocyte antigen-4 (CTLA-4), glucocorticoid-induced TNFR family-related gene (GITR), Helios and neuropilin-1 (NRP-1) as well as forkhead box protein 3 (FOXP3) were specifically expressed by these CD83(+) T cells. In contrast, CD83(-) T cells showed a naive T cell phenotype with effector T cell properties upon activation. Noteworthy, CD83(-) T cells were not able to upregulate CD83 despite activation. Furthermore, CD83(+) T cells suppressed the proliferation and inflammatory cytokine release of CD83(-) T cells in vitro. Strikingly, stimulated CD83(+) T cells released soluble CD83 (sCD83), which has been reported to possess immunosuppressive properties. In vivo, using the murine transfer colitis model we could show that CD83(+) T cells were able to suppress colitis symptoms while CD83(-) T cells possessed effector functions. In addition, this CD83 expression is also conserved on expanded human Treg. Thus, from these studies we conclude that CD83(+) T cells share important features with regulatory T cells, identifying CD83 as a novel lineage marker to discriminate between different T cell populations.
EVALuna2:1841